PENERAPAN MODEL SUPERVISI AKADEMIK UNTUK MENINGKATKAN TANGGUNG JAWAB DAN KINERJA GURU DALAM PEMEBELAJARAN ( Studi pada guru penjaskes di SMAN 2 Lahat ) - Tri Turnadi (UNIB Press, 2020)
This study aims to describe the application of the supervision model to improve the responsibility and performance of teachers in learning. This research uses the school action research method and quasi exprement. The subject of this study is the physical eduction teacher of SMAN 2 Lahat who teacher in class X, XI and XII, with 36 student class in the 2019/2020 schoool year. Data collection methods in this study use teacher observasion sheets in carrying out the learning process. Analysis of research data using descriptive statistics tha is the mean (mean) of the results of the academic suoervision model to improve the responsibility and performance of teachers in learning in improving understanding, and professionalism of teachers in the implementation of learning process.